Equilibrium with Transaction Costs - Hahn, F. H. (Econometrica, 1971)
Publisher Summary This paper examines some of the modifications required in well known propositions of general equilibrium theory when transactions require resources. Some preliminary remarks on the analysis of money in such economies are also offered.